Photocurrent generation and charge transport mechanism study in solution-processed CZTS thin films - Khanzada, Laraib S.; Makhdoom, Muhammad Atif; Lin, Xianzhong; Azimi, Hamed; Brabec, Christoph (Optik, 2023)
Clean, benign and economical energy harvesting is envisioned to mitigate the global climate change – originated from the burning of fossil fuels – addressing both the energy crises and environmental issues. In this work, charge transport mechanism and the dynamics of photocurrent generation in thin films of CZTS nanocrystals is studied. A liquid phase processing route – owing to low temperature – has been adopted using a molecular based precursor solution for the in-situ development of CZTS crystals during film deposition. Results shows that charge carriers follow band conduction and nearest-neighbor hopping (NNH) mechanisms at elevated temperatures while Mott variable-range hopping (VRH) is the dominating phenomenon at low temperatures which are analogues to expensive vacuum-deposited kieserite thin films behavior.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Conductivity; CZTS; Kesterite; Persistent photoconductivity; Solar Cell; Thin Film